Factors influencing balanced diet in patients with type 2 diabetes mellitus based on theory of planned behavior - Fentia, Lia; Ginting, Chrismis Novalinda; Chiuman, Linda (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Type 2 diabetes mellitus (DM) is a chronic disease that continues to increase globally, with a significant health and economic burden. A balanced diet is a key component of type 2 DM management. Purpose: To analyze the factors that influence balanced diet behavior in patients with type 2 DM in Pekanbaru using the Theory of Planned Behavior (TPB) approach. Method: This study used a quantitative method with a cross-sectional design. Data were collected from 117 patients with type 2 diabetes who were registered at the Pekanbaru Health Center. The variables studied included knowledge, attitude, family support, and the role of health workers in balanced diet behavior. Data analysis was performed using chi-square and Odds Ratio (OR) tests to determine the relationship and the chance of influence of independent variables on the dependent variable. Results: The results showed that low knowledge (OR=4.9), negative attitude (OR=2.5), lack of family support (OR=2.8), and non-optimal role of health workers (OR=3.2) had a significant influence on balanced diet behavior in patients with type 2 diabetes (p<0.05). Conclusion: Factors such as knowledge, attitude, family support, and the role of health workers significantly influence the balanced diet behavior of patients with type 2 diabetes. Suggestion: Education-based interventions and strengthening social support are needed to improve patient adherence to a balanced diet.